2010
DOI: 10.1111/j.1750-3841.2010.01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol‐Rich Beverages Enhance Zinc Uptake and Metallothionein Expression in Caco‐2 Cells

Abstract: The effect of red wine (RW), red grape juice (RGJ), green tea (GT), and representative polyphenols on Caco-2 cell (65)Zn uptake was explored. RW, RGJ, and GT enhanced the uptake of zinc from rice matrix. Fractionation of RW revealed that enhancing activity of zinc uptake was exclusively resided in the polyphenol fraction. Among the polyphenols tested, only tannic acid and quercitin stimulated the uptake of zinc while others did not influence the uptake. In tune with these results, only tannic acid and querciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…Another possible explanation for this behavior is based on the metal chelating ability of polyphenols, which is related to the presence of ortho-dihydroxy polyphenol, i.e., molecules bearing catechol or galloyl groups and condensed tannins; the possibility of occurrence of chelation in physiological pH also supports the physiological significance of this phenomenon [23]. In tune with our finding, in an in vitro study, polyphenol-rich beverages such as red wine, red grape juice, and green tea or certain specific polyphenols (tannic acid and quercetin) have the ability to enhance the uptake of zinc in Caco-2 cells [24]. Luminal interactions with ligands have drastic consequences for the bioavailability of metals.…”
Section: Discussionsupporting
confidence: 59%
“…Another possible explanation for this behavior is based on the metal chelating ability of polyphenols, which is related to the presence of ortho-dihydroxy polyphenol, i.e., molecules bearing catechol or galloyl groups and condensed tannins; the possibility of occurrence of chelation in physiological pH also supports the physiological significance of this phenomenon [23]. In tune with our finding, in an in vitro study, polyphenol-rich beverages such as red wine, red grape juice, and green tea or certain specific polyphenols (tannic acid and quercetin) have the ability to enhance the uptake of zinc in Caco-2 cells [24]. Luminal interactions with ligands have drastic consequences for the bioavailability of metals.…”
Section: Discussionsupporting
confidence: 59%
“…28 More recently, QCT was shown to enhance zinc uptake by Caco-2 cells, increasing total zinc accumulation and MT expression. 29 In contrast, grape seed flavonoids, produced a reduction in apical zinc uptake in Caco-2 cells, similar to that produced by phytate, whereas EGCG did not alter zinc absorption. 30 In prostate cancer cells, EGCG accelerated the accumulation of total zinc in the cytosol and mitochondria.…”
Section: Introductionmentioning
confidence: 83%
“…Similarly, the results of our current study also showed that GT had no effect on the transepithelial transport and apical uptake of 65 Zn in fully differentiated Caco-2 cells grown on microporous membrane inserts. Interestingly, a recent study proposed that green tea might enhance zinc absorption (14). The addition of green tea stimulated apical zinc uptake in intestinal Caco-2 cells grown in a 6-well plate and incubated for 3 h (14).…”
Section: Discussionmentioning
confidence: 99%
“…While bioactive dietary polyphenols are known to have no effect on zinc absorption in animals and humans (811), some studies indicated that dietary polyphenols decrease zinc absorption in animals (1213). In addition, a recent study suggested that some polyphenol-rich beverages, such as green tea, red wine and red grape juice, could enhance zinc absorption by increasing apical zinc uptake (14). Thus, while it is not clear whether dietary polyphenols affect zinc absorption, these previous studies have suggested that some dietary polyphenols may modulate intestinal zinc absorption and metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation